2021
DOI: 10.1097/cej.0000000000000708
|View full text |Cite
|
Sign up to set email alerts
|

PARP1 rs1136410 (A/G) polymorphism is associated with early age of onset of gallbladder cancer

Abstract: Objectives Evaluation of the association of PARP1 rs1136410 (A/G) polymorphism with gallbladder cancer susceptibility and its prognosis in the Indian population of eastern Uttar Pradesh and western Bihar. Methods PARP1 rs1136410 was genotyped by PCR-RFLP and its association with the prognosis of gallbladder cancer patients were analyzed using Kaplan–Meier plot and log-rank tests. Results Our results demonstrate that minor allele G is more frequent in gallbladder cancer patients than controls. The frequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“… 97–99 Several studies have studied molecular features of early-onset biliary tract cancer ( Table 2 ). 83 , 84 …”
Section: Current Evidence Of Early-onset Digestive System Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“… 97–99 Several studies have studied molecular features of early-onset biliary tract cancer ( Table 2 ). 83 , 84 …”
Section: Current Evidence Of Early-onset Digestive System Cancersmentioning
confidence: 99%
“… 83 A study of gallbladder cancer by Kumari et al suggested that a minor allele G and homozygous genotype GG of PARP1 rs1136410 (A/G) are significantly associated with the development of gallbladder carcinoma in younger adults. 84 …”
Section: Current Evidence Of Early-onset Digestive System Cancersmentioning
confidence: 99%